Oscillating reactions at metal electrodes in solid electrolytes - Janek, Jürgen; Justus Liebig University Giessen (My University, 1997)
The transfer of matter and charge across interfaces between two solids is generally related to processes of defect relaxation in the regions near the interface. A transfer rate which exceeds the rate of defect relaxation may lead to degradation of the interface, causing a feedback effect for the transfer itself. As a consequence, non-linear phenomena (dissipative structures) like periodic oscillations of the interfacial properties can occur under conditions far from equilibrium. Experimental examples are discussed.
Keywords: Dissipative structures; Electrochemical oscillations; Interfaces; Ionic conductors; Point defects; ddc:540